The Most Popular Videos Promoting Breast Enhancement Products on TikTok: Cross-Sectional Content and User Engagement Analysis - Jing Lin; Wanlin Li; Lian Zhu; Ning Li; Shi Chang (Journal of Medical Internet Research)
Abstract BackgroundThe proliferation of health-related content on social media platforms has changed the way people access and interpret information about cosmetic medicine. TikTok (ByteDance) has become an important platform for sharing breast enhancement content, yet little is known about the quality, credibility, and impact of such information on user perceptions and decision-making. ObjectiveThis paper aims to analyze the characteristics of breast enhancement videos, including uploader demographics, product details, promotional claims, and user engagements, to better understand the nature of the claims and products encountered by users. MethodsWe conducted a cross-sectional content analysis of the top 150 most-liked breast enhancement videos via TikTok’s web interface. The videos were coded according to the uploader’s traits (gender expression and account type), product details (type and scientific evidence), and promotional strategies (testimonials and sponsorship disclosures). Engagement metrics (likes and shares) were recorded, and nonparametric tests (Mann–Whitney U ResultsOverall, 85 videos were included in the final analysis, with most uploaders presenting a feminine gender expression (59/85, 69.4%) and using uncertified content creator accounts (59/85, 69.4%). The most promoted product types were breast enhancement creams or oils (32/85, 37.6%) and breast implants (22/85, 25.9%). Most videos (71/85, 83.5%) depicted the products positively; however, most videos (78/85, 91.8%) provided no scientific evidence of the product’s efficacy. Engagement metrics revealed that videos by licensed physicians received significantly higher thumbs up (median 9761, IQR 4975-19,492) than uncertified content creator uploaders (median 701, IQR 280‐2604; P ConclusionsTikTok’s short video format fosters widespread and rapid dissemination of breast enhancement information, representing a key strength in democratizing health communication. Its user-friendly interface and visual appeal also offer a valuable avenue for medical professionals to engage audiences more dynamically. However, the lack of rigorous content checks can amplify misleading or unverified claims. To address these weaknesses, implementing dual-mode content review could be essential for maximizing TikTok’s capacity to support informed public health decision-making.